Bio-inspired synthesis of Co-doped CuO/ZnO nanocomposites for enhanced photocatalytic degradation of methyl blue - Samrawit Mekonen Yimer; Ashenafi Zeleke Melaku (Results in Chemistry)
Environmental pollution by organic dyes poses a significant global threat, necessitating sustainable remediation techniques. This study reports the green synthesis of a novel cobalt-doped CuO/ZnO nanocomposite using Hagenia abyssinica leaf extract as a bioreducing and capping agent, offering an eco-friendly alternative to traditional methods. The synthesized nanocomposite was characterized by XRD, FTIR, SEM-EDX, and UV–Vis DRS. XRD confirmed the successful formation of Co-doped CuO/ZnO with distinct peaks indicating cobalt incorporation and enhanced crystallinity. Confirmation of cobalt integration into the CuO/ZnO nanocomposite is provided by two key observations: a new peak appearing around 31∘, and shifts in the peak positions at both 29.4∘ and 31.7∘. These changes also point to an alteration in the crystallinity of the material. Additionally, the distinctive metal (Co, Cu, Zn)‑oxygen stretching peaks are visible in the FT-IR spectrum between 500 and 900 nm wavelengths. FTIR analysis verified the role of phytochemicals in stabilization, while SEM-EDX result revealed uniformly distributed elements of nanoparticles. Optical properties from UV–Vis DRS spectrum showed that cobalt doping effectively reduced the bandgap of CuO/ZnO, enabling efficient sunlight absorption. Photocatalytic degradation tests demonstrated that the Co-doped CuO/ZnO nanocomposite significantly enhanced the degradation of methyl blue dye. Notably 2 mg of 0.05 %Co-5 %CuO/ZnO exhibited superior activity (93.82 % degradation of 10 mg MB in 80 min) compared to pristine ZnO (57.2 %), attributed to reduced electron-hole recombination and optimized bandgap. This bio-mediated approach offers a promising, sustainable solution for industrial wastewater treatment.